2019
DOI: 10.1371/journal.pone.0222292
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide analysis of methylation in giant pandas with cataract by methylation-dependent restriction-site associated DNA sequencing (MethylRAD)

Abstract: The giant panda (Ailuropoda melanoleuca) is a native species to China. They are rare and endangered and are regarded as the ‘national treasure’ and ‘living fossil’ in China. For the time being, there are only about 2500 giant pandas in the world. Therefore, we still have to do much more efforts to protect the giant pandas. In captive wildlife, the cataract incidence of mammalian always increases with age. Currently, in China, the proportion of elderly giant pandas who suffering from cataract has reached 20%. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

6
1

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…Although genetic factors have been identified that promote age-related cataracts, the most important triggers are environmental, particularly oxidative stress and DNA damage [ 7 – 10 ]. We previously compared the DNA methylation status of giant pandas with and without cataracts in an attempt to identify epigenetic effects that might influence the expression of genes associated with cataract formation [ 17 ]. We identified multiple differentially methylated genes with potential roles in cataract-related pathways, including base excision repair, apoptosis and p53 signaling.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although genetic factors have been identified that promote age-related cataracts, the most important triggers are environmental, particularly oxidative stress and DNA damage [ 7 – 10 ]. We previously compared the DNA methylation status of giant pandas with and without cataracts in an attempt to identify epigenetic effects that might influence the expression of genes associated with cataract formation [ 17 ]. We identified multiple differentially methylated genes with potential roles in cataract-related pathways, including base excision repair, apoptosis and p53 signaling.…”
Section: Discussionmentioning
confidence: 99%
“…The genes most strongly associated with cataracts therefore include those related to oxidative stress responses, the production of antioxidant enzymes and metabolites, and various DNA repair pathways [ 11 – 13 ]. Previous studies identified changes in DNA methylation associated with cataract formation in several mammals [ 14 – 16 ] and we recently reported that 110 genes with functions relevant to cataract pathogenesis are differentially methylated in giant pandas, including six genes known to be associated with age-related cataracts in humans [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon has been observed in companion animals: for example, cataract development in dogs is often associated with diabetes, obesity, prolonged use of corticosteroid, excessive exposure to sunlight, or previous eye injury/inflammation [ 52 , 53 ]. It is therefore unclear whether cataracts in captive pandas are age-related acquired or congenital lesions due to the absence of suitable genetic markers [ 54 ]. Here we used a functional candidate gene screening approach to test 11 known cataract-associated genes in giant panda specimens with and without cataracts.…”
Section: Introductionmentioning
confidence: 99%
“…Although mutations affecting MIP have been shown to cause congenital cataracts in humans and mice, analogous mutations have not been reported in the giant panda (Ailuropoda melanoleuca). These animals tend to develop cataracts in captivity because they live much longer than their counterparts in the wild, but it is often unclear whether these are age-related or congenital lesions due to the absence of suitable disease markers (You et al 2019). Here we used a functional candidate gene screening approach to test for known cataract-associated genes in giant panda specimens with cataracts.…”
Section: Introductionmentioning
confidence: 99%